Life Cycle Assessment of Melon (Cucumis Melo L) Production in Tropical Greenhouse, Indonesia - Supriyanto Supriyanto; Arkandithya Naufal Pratama; Erniati Erniati; Lilis Sucahyo (The University of Lampung, 2025)
Recently, melon cultivation in controlled environments such as greenhouse are popular to improve productivity and quality. However, environmentally friendly productions are necessary for preserving ecosystems and reducing environmental impact. This research aimed to evaluate the environmental impact using a life cycle assessment approach. Research was conducted using a life cycle assessment with six categories evaluated such as Global Warming Potential (GWP), Stratospheric Ozone Depletion (SOD), Terrestrial Acidification (TAC), Freshwater Eutrophication (FEU), Terrestrial Ecotoxicity (TEC), and Human Carcinogenic Toxicity (HCT) for kilograms of fresh melon. The result of GWP was 2.137 kg CO2 eq; SOD at 0.39(10-5) kg CFC-11 eq; TAC at 3.93(10-3) kg SO2 eq; FEU at 0.44(10-3) kg P eq; TEC at 4.62 kg 1.4-DCB eq; and HCT at 0.13 kg 1.4-DCB eq. Furthermore, the main contribution of environmental impact was cultivating media such as cocopeat and rice husk charcoal. The result of this research is important to improve greenhouse-based melon production. Keywords: Greenhouse, GWP, Life cycle assessment, Melon.